Algorithmic models of distributed simulation process for technology analysis of distributed simulation models - Волк, Максим Александрович; Гридель, Ростислав Николаевич; Саранча, Сергей Николаевич; Гавриш, Денис Александрович (Eastern-European Journal of Enterprise Technologies, 2013)
Despite the widespread use of the distributed simulation, little attention has been paid to the construction of effective models of the distributed simulation itself and based on them analysis of the task flows in the systems of the cloud computing level with the purpose of obtaining the parameters and characteristics, used in task planners, resource brokers, scheduling algorithms. The algorithmic model for the distributed simulation process, providing the extended set of the key parameters of the model is first proposed in the paper. The model is based on the software representation of the simulation environment of modeling in the form of the set of executable code (activities of the particular model) and data (internal and external parameters, environment variables, data flows between particular models). The proposed model first considers the actual time, taken for the performance of particular models, dynamic memory capacity in the course of experiments, idle time of resources and other parameters. It is shown that on the basis of the proposed algorithm, it is possible to create a number of methods for the analysis of the distributed simulation models, the set of which allows to develop new technology of the analysis of the distributed simulation models. The obtained results can be used in modern information technologies of the distributed simulation, in particular for the construction of the subsystem of distribution and dynamic redistribution of computing resources.